DEVELOPMENT OF A PROBLEM BASED LEARNING E-MODULE WITH THE ASSISTANCE OF CANVA ON THE MATERY OF BALANCE AND ROTATIONAL DYNAMICS TO GROW STUDENTS' INTEREST IN LEARNING - Senja, Bone Komala; Medriati, Rosane; Putri, Desy Hanisa (Universitas Tanjungpura, 2024)
This study aims to determine the feasibility of developing the Problem Based Learning e-module developed using canva to foster student interest in learning. This research method uses RD research with the ADDIE type. The instruments used were observation, interviews and needs analysis questionnaires which obtained results of 81.04% with categories strongly agreeing to develop e-modules. The design of the e-module learning media will be developed according to what has been prepared. Expert validation sheet instruments consisting of aspects of content feasibility, material presentation, language, media, PBL and interest in learning can be seen that the development of e-modules is very feasible with an average percentage of 88.54% and student perception results which has 3 aspects, namely the appearance, presentation of material and benefits has an average yield of 81.81% of 3 Bengkulu City High Schools which can be categorized as very good. It can therefore be concluded that the development of the E-module Problem Based Learning assisted by Canva on the material of balance and rotational dynamics to foster students' interest in learning becomes a very viable product.